Foliar nutrient concentrations and resorption efficiency in plants of contrasting nutrient‐acquisition strategies along a 2‐million‐year dune chronosequence. (10th December 2013) - Hayes, Patrick; Turner, Benjamin L.; Lambers, Hans; Laliberté, Etienne; Bellingham, Peter
Summary Long‐term pedogenesis leads to important changes in the availability of soil nutrients, especially nitrogen (N) and phosphorus (P). Changes in the availability of micronutrients can also occur, but are less well understood. We explored whether changes in leaf nutrient concentrations and resorption were consistent with a shift from N to P limitation of plant productivity with soil age along a > 2‐million‐year dune chronosequence in south‐western Australia. We also compared these traits among plants of contrasting nutrient‐acquisition strategies, focusing on N, P and micronutrients. The range in leaf [P] for individual species along the chronosequence was exceptionally large for both green (103–3000 μg P g−1) and senesced (19–5600 μg P g−1) leaves, almost equalling that found globally. From the youngest to the oldest soil, cover‐weighted mean leaf [P] declined from 1840 to 228 μg P g−1, while P‐resorption efficiency increased from 0% to 79%. All species converged towards a highly conservative P‐use strategy on the oldest soils. Declines in cover‐weighted mean leaf [N] with soil age were less strong than for leaf [P], ranging from 13.4 mg N g−1 on the youngest soil to 9.5 mg N g−1 on the oldest soil. However, mean leaf N‐resorption efficiency was greatest (45%) on the youngest, N‐poor soils. Leaf N:P ratio increased from 8 on the youngest soil to 42 on the oldest soil. Leaf zinc (Zn) concentrations were low across all chronosequence stages, but mean Zn‐resorption efficiency was greatest (55–74%) on the youngest calcareous dunes, reflecting low Zn availability at high pH. N2‐fixing species had high leaf [N] compared with other species. Non‐mycorrhizal species had very low leaf [P] and accumulated Mn across all soils. We surmise that this reflects Mn solubilization by organic acids released for P acquisition. Synthesis. Our results show community‐wide variation in leaf nutrient concentrations and resorption that is consistent with a shift from N to P limitation during long‐term ecosystem development. High Zn resorption on young calcareous dunes supports the possibility of micronutrient co‐limitation. High leaf [Mn] on older dunes suggests the importance of carboxylate release for P acquisition. Our results show a strong effect of soil nutrient availability on nutrient‐use efficiency and reveal considerable differences among plants of contrasting nutrient‐acquisition strategies.